Takayasu’s Arteritis - Rajbhandari, Sujeeb (Nepalese Heart Journal, 2017)
Takayasu’s arteritis is a disease of unknown etiology primarily affecting women aged less than 40 years. It is mainly seen in Asians and Africans. This condition is an aorto-arteritis and involves aorta and its major branches causing segmental narrowing or dilatation. Diminished or absent pulses and hypertension are common. Constitutional symptoms, including fever and weight loss, are often accompanied by elevation of acute phase markers. Diagnosis is made usually in quiescent or “cold phase” of the disease. Long-term complications are due mainly to arterial occlusion and related damage, including limb ischemia and renal failure.